Assessing Glutathione-S-Transferase Levels In Serum with Oral Malignancy Patients - Shubham Patil, Virvardhan Alias; Salyam, Vinay; Akshitha, Manda; Saini, Gourav; Dave, Aparna; Saluja, Pulin (Journal of Neonatal Surgery, 2025)
Background: Glutathione-S-transferases (GSTs) are a family of detoxifying enzymes that play a critical role in cellular defense mechanisms against oxidative stress and carcinogenic agents. Alterations in GST activity have been implicated in the pathogenesis of various malignancies, including oral cancer. This study aims to assess and compare serum GST levels in patients diagnosed with oral malignancy versus healthy individuals to explore its potential as a biomarker for early detection and progression of disease. Materials and Methods: A total of 60 participants were included in this cross-sectional study, comprising 30 patients with histologically confirmed oral squamous cell carcinoma (Group A) and 30 age- and sex-matched healthy controls (Group B). Blood samples were collected, and serum GST levels were measured using an ELISA-based immunoassay. Clinical parameters including tumor site, TNM stage, and tobacco use history were recorded. Statistical analysis was performed using independent t-tests and one-way ANOVA for subgroup comparisons, with a significance threshold of p<0.05. Results: The mean serum GST level in Group A was significantly elevated (12.45 ± 2.36 U/L) compared to Group B (6.78 ± 1.15 U/L) (p<0.001). A positive correlation was observed between GST levels and advanced TNM staging (Stage III and IV showed a mean GST level of 14.21 ± 1.85 U/L). Tobacco users among oral cancer patients had higher GST levels (13.56 ± 1.90 U/L) than non-users (10.87 ± 2.14 U/L), suggesting a synergistic effect of tobacco-induced oxidative stress. Conclusion: Serum glutathione-S-transferase levels are significantly elevated in patients with oral malignancy and correlate with disease progression and tobacco exposure. GST may serve as a potential biomarker for early diagnosis, risk assessment, and monitoring of therapeutic response in oral cancer patients